Machine Creativity in Terms of Detachment, Withdrawal, and Renunciation - Olszewska, Anna (Transformations, 2022)
This paper argues that the ongoing debate on artificial creativity has largely overlooked the passive component of creation. The study questions the discussion of inventiveness merely as an act resulting in multiplication of artefacts, ideas and methods. Alternatively, it suggests expanding the artificial creativity discourse to include concepts of detachment, withdrawal, and renunciation. The proposed approach implies that an artificial system’s creativity may arise from the withholding of movement or an energy flow reversion. Renunciation of routine activities and detachment from the external environment resulting from those processes can be accomplished either by a reflexive subject or a machine. To envisage how artificial creativity programmes could profit from exploration of the passive aspects of creativity, the paper reviews manifestos, artistic interventions and blueprints that test the technical domain on its completeness, limitations and self- sufficiency. The discussed examples of artistic interventions into the technical sphere come from artists such as !Mediengruppe Bitnik, Guido Segni, Sam Lavigne and John F Simon, together with the critical essays of Timothy J. Clark, McKenzie Wark and Silvio Lorusso. The paper looks at renunciation patterns and artistic interventions as if they were games played either by human or non-human actors. The text reconstructs the roles behind the scripts and the mythologies of technicity in order to infer how non-actual is used in human-machine relation. The study provides a set of arguments for those who discuss alternatives to AI or artificial creativity projects.